Results that last : hardwiring behaviors that will take your company to the top - Studer, Quint (Hoboken, N.J. : J. Wiley & Sons, 2008)
Praise For Results That Last. "Quint Studer is a superb communicator with a deep belief in the power of relationships. His informal tone, sense of humor, and real-world stories bring his business principles to life. Results That Last has a vital, optimistic quality that will keep readers re-reading long after other leadership books have been relegated to a dark corner of the shelf."--Nido Qubein, author of How to Get Anything You Want; President, High Point University; Chairman, Great Harvest Bread Company; and founder, National Speakers Association Foundation. "Results That La
RESULTS THAT LAST; Contents; Introduction; KEY TACTICS; THE CORE; EMPLOYEE TACTICS; CUSTOMER TACTICS; About Studer Group; Other Leadership Books By Quint Studer and Studer Group; Index.
Print version record.
English.
John Wiley and Sons
Keywords: Leadership; Organizational behavior; Corporate culture; Personnel management; Executives; Leadership; Organizational Culture; Personnel Management; Administrative Personnel; Leadership; Comportement organisationnel; Culture organisationnelle; Personnel -- Direction; Cadres (Personnel); executives; BUSINESS & ECONOMICS -- Leadership; Personnel management; Executives; Corporate culture; Leadership; Organizational behavior